Psychosocial Interventions for Amphetamine Type Stimulant Use Disorder: An Overview of Systematic Reviews - Tran, Mai Thi Ngoc; Luong, Quang Hung; Le Minh, Giang; Dunne, Michael P.; Baker, Philip (Frontiers in Psychiatry, 2021)
Introduction: Amphetamine-type stimulants (ATS) use is a global concern due to increased usage and the harm to physical, mental and social wellbeing. The objective of this overview of systematic reviews is to summarise trial results of psychosocial interventions and describe their efficacy and safety. Methods: We searched seven bibliographic databases to November 2020 for systematic reviews examining ATS misuse treatment by psychosocial interventions. Given the apparent incompleteness of the included reviews, we undertook a supplemental meta-analysis of all eligible primary studies. Results: We included 11 systematic reviews of moderate to high quality and 39 primary studies which assessed the outcomes of psychosocial interventions on people who use ATS. The key findings include: (1) There were conflicting results about the effectiveness of psychosocial interventions among reviews, which may confuse decision-makers in selecting treatment. (2) In the supplemental meta-analysis, relative to usual care (only counselling or self-help materials), membership of a psychological intervention group was associated with an important reduction in drug usage (risk ratio (RR) 0.80, 95% CI: 0.75 to 0.85). Patients in psychological interventions used injectables substantially less (odds ratio (OR) 0.35, 95% CI: 0.24 to 0.49). The risk of unsafe sex in the psychosocial intervention group was lower than in the control group (RR 0.49, 95% CI: 0.34 to 0.71). The combination of therapies reduced 1.51 day using drugs in the preceding 30 days (95% CI: -2.36 to -0.67) compared to cognitive behavioural therapy intervention alone. (3) Compared to usual care, cognitive behavioural therapy was less likely to be retained at follow-up (RR 0.89, 95% CI: 0.82 to 0.97; high-quality evidence). However, the additional of contingency management strategy can make an important improvement upon retention (RR 1.42, 95%CI: 1.25 to 1.62). Authors’ Conclusions Integrated models are more effective than a single-treatment strategy. Comprehensive and sustained psychosocial interventions can help to reduce use of ATS and other drugs, risk behaviours and mental disorders, and significantly improve treatment adherence.